2013
DOI: 10.1111/aje.12110
|View full text |Cite
|
Sign up to set email alerts
|

Will climate warming exceed lethal photosynthetic temperature thresholds of lichens in a southern African arid region?

Abstract: Predicted elevated temperatures and a shift from a winter to summer rainfall pattern associated with global warming could result in the exposure of hydrated lichens during summer to more numerous temperature extremes that exceed their thermal thresholds. This hypothesis was tested by measuring lethal temperature thresholds under laboratory and natural conditions for four epilithic lichen species (Xanthoparmelia austro-africana, X. hyporhytida, Xanthoparmelia sp., Xanthomaculina hottentotta) occurring on quartz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As a consequence, lichen net photosynthesis has an optimal temperature above which further increases in respiration depress net carbon gain, and it has been shown that net CO 2 exchange can become negative at moderately elevated temperatures (Green & Lange, 1994). Lethal temperatures for photosynthesis in active, hydrated lichens are not high, usually around 30-35°C (Chiarucci, Calderisi, Casini, & Bonini, 2008;Lange, 1965;Maphangwa, Musil, Raitt, & Zedda, 2014;Smith, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, lichen net photosynthesis has an optimal temperature above which further increases in respiration depress net carbon gain, and it has been shown that net CO 2 exchange can become negative at moderately elevated temperatures (Green & Lange, 1994). Lethal temperatures for photosynthesis in active, hydrated lichens are not high, usually around 30-35°C (Chiarucci, Calderisi, Casini, & Bonini, 2008;Lange, 1965;Maphangwa, Musil, Raitt, & Zedda, 2014;Smith, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resistance to heat stress certainly depends on lichen species. For example, in lichens from the arid region of South Africa, the lethal temperature ranged between 44.1 and 48.1 °C 48 . In contrast, Marin et al .…”
Section: Discussionmentioning
confidence: 99%
“…We found that most within-species variation in lichen habitat relationships revealed plastic adaptation to available combinations of ecological factors, rather than evolutionary lineages. This highlights regional ecosystem integrity, resilience, and related risk assessments (long-term trends; disasters; novel threats) as a major approach for lichen conservation (e.g., [ 266 , 267 , 268 ]), for which sensitive species might serve as indicators [ 269 ].…”
Section: Conservation Implicationsmentioning
confidence: 99%